Detection leakage of buried diesel passage by the electrical properties in various soil / Muhammad Aiman Asyraf Jaif - Jaif, Muhammad Aiman Asyraf (2019)
The most crucial parameter to be investigated for environmental engineering survey was the electrical conductivity of the sub-surface material by using Ground Penetrating Radar (GPR). The factors that affected soil contamination parameter were soil moisture content which caused the electrical conductivity diversity in time propagation. The main of objective of this research was achieved which is detect diesel, leakage in different type of soil, detection diesel leakage through electrical conductivity and analysed of electrical properties of diesel leaks detection in various type of soil in this research. GPR method was used to gain the electrical conductivity variation with aid of analysis regarding the time-based of diesel presence that interacted relatively with the soil moisture. Diesel filled to contaminate the soil of Cherang hangus, Terap red and sand. GPR measurement carried out by using 800MHz frequency while soil moisture reading recorded during scanning. Diesel caused a high loss of electromagnetic wave scattering, but sometimes increased the radar signal amplitude, and lead the electrical conductivity to its higher value for larger increment of soil moisture at the saturated soil. It is proved that soil will be dry after mixed with diesel, it caused the electrical conductivity increased among the time.